(untitled) (Journal of Global Accounting, 2022)
This study examined the relationship between Naira foreign exchange rate and investors’ confidence in Nigeria stock market from 2005 to 2020. The volume and value of traded securities were used as proxies for investors’ confidence. The study made use of secondary data sourced from Nigerian Stock Exchange (NSE) facts book and Central Bank of Nigerian statistical bulletin for various years. The data were analyzed using pie chart, while the formulated hypotheses were regressed with the help of e-view package. From the result it was ascertained that Naira exchange rate has negative and insignificant relationship with investors’ confidence. The positive aspect of the result is that government and institutions can resort back to the stock market as a cheap source of fund instead of borrowing externally with the prevalent high exchange rate. The study recommends creation of more investment outlets or opportunities including retail and consumer outlets where people can invest as individuals and corporate bodies. Again capital market awareness creation about the available investment opportunities shouldn’t be neglected as it is capable of attracting both foreign portfolio and local investors.